Relation between Nose Scale and Sleep Disorder Breathing Among Spice Factory Workers in Semarang - Indra Pratama Dana; Kanti Yunika (Jurnal Kesehatan Masyarakat, 2025)
Sleep-disorder breathing covers a broad spectrum of breathing-related sleep disorders. Nasal obstruction has been identified as a modifiable risk of sleep-disordered breathing and is a common complaint in sleep-disordered breathing patients. The nose scale is a simple standard instrument that can estimate those at risk of developing sleep-disordered breathing. To determine the relationship between nose scale and sleep disorder breathing in spice factory workers in Semarang. Analytical observational research with a cross-sectional design involving 530 spice factory workers in Semarang. The independent variable of the study was the risk of developing sleep-disordered breathing based on the body mass index value. The dependent variable of the research is the Nose Scale score. Analysis was by the Independent T-test, Mann- Whitney, Chi-square, and Fisher exact tests. Results are significant if p<0.05. Complaints of a blocked nose (6% vs 3%), blocked nose (8% vs 7%), difficulty breathing (4% vs 3%), difficulty sleeping due to nasal problems (5% vs 3%), and difficulty breathing air (6 % vs 4%) was more common in the high risk sleep disorder breathing group (BMI >25kg/m2) than in the low risk sleep disorder breathing group (BMI <25kg/m2), respectively. The high risk sleep disorder breathing group (BMI >25kg/m2) also reported a higher mean Nose Scale score than the low risk sleep disorder breathing group (BMI <25kg/m2), namely 5.81 vs 3.95. Individuals with high risk sleep disorder breathing (BMI >25kg/m2) have higher complaints of nasal problems than individuals with low risk sleep disorder breathing (BMI <25kg/m2).